Opto-electronic bias of a superconducting nanowire single photon detector using a cryogenic photodiode - Thiele, Frederik; Hummel, Thomas; Protte, Maximilian; Bartley, Tim (APL Photonics)
Superconducting Nanowire Single Photon Detectors (SNSPDs) have become an integral part of quantum optics in recent years because of their high performance in single photon detection. We present a method to replace the electrical input by supplying the required bias current via the photocurrent of a photodiode situated on the cold stage of the cryostat. Light is guided to the bias photodiode through an optical fiber, which enables a lower thermal conduction and galvanic isolation between room temperature and the cold stage. We show that an off-the-shelf InGaAs–InP photodiode exhibits a responsivity of at least 0.55 A/W at 0.8 K. Using this device to bias an SNSPD, we characterize the count rate dependent on the optical power incident on the photodiode. This configuration of the SNSPD and photodiode shows an expected plateau in the single photon count rate with an optical bias power on the photodiode above 6.8 µW. Furthermore, we compare the same detector under both optical and electrical bias, and show there is no significant changes in performance. This has the advantage of avoiding an electrical input cable, which reduces the latent heat load by a factor of 100 and, in principle, allows for low loss RF current supply at the cold stage.
Keywords: Computer Networks and Communications; Atomic and Molecular Physics; and Optics

Knowledge Equity and Open Science in qualitative research – Practical research considerations - Steinhardt, Isabel; Kruschick, Felicitas (Research Ideas and Outcomes)
How can Knowledge In/Equity be addressed in qualitative research by taking the idea of Open Science into account? Two projects from the Open Science Fellows Programme by Wikimedia Deutschland will be used to illustrate how Open Science practices can succeed in qualitative research, thereby reducing In/Equity. In this context, In/Equity is considered as a fair and equal representation of people, their knowledge and insights and comprehends questions about how epistemic, structural, institutional and personal biases generate and shape knowledge as guidance. Three questions guide this approach: firstly, what do we understand by In/Equity in the context of knowledge production in these projects? Secondly, who will be involved in knowledge generation and to what extent will they be valued or unvalued? Thirdly, how can data be made accessible for re-use to enable true participation and sharing?
Keywords: Open Science; Knowledge Equity; Qualitative Methods

Die (Un-)Sichtbarkeit von (offenen) Bildungsmaterialien in der Soziologie - Hiebl, Johannes; Steinhardt, Isabel; Bigos, Michael (die hochschule)
Der Beitrag beschäftigt sich mit dem Gebrauch von sogenannten Open Educational Resources (OER) innerhalb der deutschsprachigen Soziologie. OER sind Lehr-und Lernmaterialien, die öffent-lich und frei von Kosten zugänglich sind sowie unter einer offenen Lizenz stehen, die es erlaubt, das Material frei zu nutzen, zu vervielfältigen und zu bearbeiten. Um diese Form der Bereitstellung von Lehr-und Lernmaterial zu fördern, sind im deutschen Sprachraum in den letzten Jahren verschie-dene digitale Infrastrukturen entstanden, die an einzelnen Hochschulstandorten, aber auch hochschulübergreifend Lehrenden zur Verfügung stehen, um dort ihr Material zu veröffentlichen. Es wurden 37 dieser Repositorien untersucht. Darüber hinaus wurde auch die Videoplattform YouTube nach soziologischem Lehr-und Lernmaterial durchforstet. Der Beitrag stellt den Zeitverlauf und die Akteur:innen der OER-Veröffentlichungen dar. Anschließend soll mithilfe eines praxistheoretischen Vokabulars die Lehre innerhalb der Soziologie aufgeschlüsselt und ein möglicher Bezug zu den empirischen Ergebnissen hergestellt werden.
Keywords: Soziologie; Praxistheorie; Repositorien; Open Educational Resources; OER

Dem eigenen Anspruch auf der Spur - Ternes, Doris; Bernhard, Nadine; Gewinner, Irina; Goller, Antje; Lohner, David; König, Karsten; Röwert, Ronny; Steinhardt, Isabel; Thielsch, Angelika (Hochschulen in der Pandemie. Impulse für eine nachhaltige Entwicklung von Studium und Lehre)
Der Beitrag geht der Frage nach, welchen Herausforderungen Lehrende durch die digitale Lehre im ersten Corona-Semester 2020 begegnet sind und welche Strategien sie für deren Bewältigung gewählt haben. Als Datengrundlage dienendazu sechs autoethnographische Stories, entstanden im Projekt AEDiL. Diese haben sich als wertvolles Material erwiesen, um unmittelbare Einblicke in das Lehrhandeln und die -planung zu erhalten und die weiterführende Analyse zu ermöglichen. Dabei offenbarte sich der gemeinsame Anspruch der studierenden-zentrierten Lehre als wiederkehrendes Muster. Die mehrstufige Analyse legt offen, wie Lehrpersonen mit den Themen Beziehungsaufbau, Schaffung eines (digitalen) Raums sowie Sicherheit für Studierende umgehen und sich daraus Handlungsmuster entwickeln.

Die Kraft der Bilder. Funktionen neuer Illustrationen bei Übersetzungen. Kathleen Vereecken – Alles komt goed, altijd (2018) | Alles wird gut, immer (2021) - Lammer, Christina
Keywords: Kathleen Vereecken; Kinder- und Jugendliteratur; Krieg; Belgien

Assessment of Energy Efficiency and Flexibility Measures in Electrified Process Heat Generation Based on Simulations in the Animal Feed Industry - Knorr, Lukas; Schlosser, Florian; Meschede, Henning

Von lebenden Systemen und gefühlten Zahlen. Eine körpersoziologische Analyse des finanzaufsichtlichen Risikobewertungsregimes - Knoll, Lisa (Österreichische Zeitschrift für Soziologie)
Der hier vorliegende Beitrag erarbeitet Verbindungslinien zwischen Wirtschaftssoziologie (insb. Finanzsoziologie), Soziologie der Bewertung und Körpersoziologie anhand des Falls finanzmarktregulatorischer Risikobewertung. Dabei spielt der analytische Begriff der Prothese (Michel Callon) eine wichtige Rolle. Nach der Finanzkrise kommt es zu einer Neuverteilung von sensorischen Bewertungskompetenzen in einer hierarchisch aufgebauten, vernetzten Wissensarchitektur. Es ist nun die Maschine, der Lebendigkeit attestiert wird, während der Mensch parzellierte Funktionen in einer Apparatur übernimmt. Gleichzeitig soll der Mensch so zu einem adäquaten und beweglichen (spielerischen) Umgang mit Risiken angeregt werden, die man ihm/ihr in einem eher groben und einfachen Aufsichtssystem nicht mehr zutraute (hier wurden „regulatory arbitrage“ und „kreative Buchführung“ zum Problem). Der Aufsatz rekonstruiert die praktischen Orientierungen und kollektiven Erfahrungen dieses finanzaufsichtlichen Umbaus anhand zweier problemzentrierter Interviews. Unter Rekurs auf die Körperbezüge in diesen Interviews wird die Paradoxie eines Systems herausgearbeitet, das nach wie vor auf individuelle Entscheidungsrationalität und -agilität setzt, diese nun aber maschinell zu erschaffen sucht.
Keywords: General Social Sciences

Zweierlei Homophilie: Wendy Hui Kyong Chun und Leo Bersani - Althoff, Sebastian (Mimesis Expanded: Die Ausweitung der mimetischen Zone)

Musterbildungen. Ein alternativer Zugang zur Fernsehgeschichte: Über Lynn Spigels TV Snapshots – An Archive of Everyday Life - Miggelbrink, Monique (Cargo H. 56)

The DaimlerChrysler takeover failure revisited from a varieties-of-capitalism perspective - Riach, John Rankin Wood; Schneider, Martin (Cross Cultural and Strategic Management)
Purpose The purpose of this paper is to revisit the disastrous DaimlerChrysler AG takeover episode from 1998 to 2007 in order to arrive at a more comprehensive explanation of this and other merger and takeover failures based on institutional theory. Design/methodology/approach The case study is based on various secondary sources of information and on the insights that one of the authors gained from working for 14 years in various positions for Daimler-Benz and DaimlerChrysler. Findings DaimlerChrysler failed because top management made mistakes in trying to globalize the company. They were unable to realize possible synergies between the two companies, which brought complementary resources into the merger. Furthermore, they did not account for the institutional embeddedness of strategies when they adopted lean production globally, diffused the production system developed in Germany to other parts of the world and tried to implement a global stock enlisted in New York and Frankfurt. The underlying theoretical framework is relevant for other merger and acquisition cases. It features institutional embeddedness, path dependency and institutional arbitrage. Originality/value The paper develops an institutional perspective on DaimlerChrysler and on cross-border merger and acquisition failure more generally. The perspective is organized around the varieties-of-capitalism approach. This contribution is important because there is increasing dissatisfaction with the dominant explanation of cross-border merger and acquisition failure, which is based on the allegedly failed management of culture “clashes.”
Keywords: Organizational Behavior and Human Resource Management; Strategy and Management; Sociology and Political Science; Cultural Studies; Business and International Management

Dequantizing the Quantum Singular Value Transformation: Hardness and Applications to Quantum Chemistry and the Quantum PCP Conjecture - Gharibian, Sevag; Gall, François Le (Proceedings of the 54th ACM Symposium on Theory of Computing (STOC))
The Quantum Singular Value Transformation (QSVT) is a recent technique that gives a unified framework to describe most quantum algorithms discovered so far, and may lead to the development of novel quantum algorithms. In this paper we investigate the hardness of classically simulating the QSVT. A recent result by Chia, Gily\'en, Li, Lin, Tang and Wang (STOC 2020) showed that the QSVT can be efficiently "dequantized" for low-rank matrices, and discussed its implication to quantum machine learning. In this work, motivated by establishing the superiority of quantum algorithms for quantum chemistry and making progress on the quantum PCP conjecture, we focus on the other main class of matrices considered in applications of the QSVT, sparse matrices. We first show how to efficiently "dequantize", with arbitrarily small constant precision, the QSVT associated with a low-degree polynomial. We apply this technique to design classical algorithms that estimate, with constant precision, the singular values of a sparse matrix. We show in particular that a central computational problem considered by quantum algorithms for quantum chemistry (estimating the ground state energy of a local Hamiltonian when given, as an additional input, a state sufficiently close to the ground state) can be solved efficiently with constant precision on a classical computer. As a complementary result, we prove that with inverse-polynomial precision, the same problem becomes BQP-complete. This gives theoretical evidence for the superiority of quantum algorithms for chemistry, and strongly suggests that said superiority stems from the improved precision achievable in the quantum setting. We also discuss how this dequantization technique may help make progress on the central quantum PCP conjecture.

Ich. Das bin ich! Zugehörigkeit, Freundschaft und Familie. Zyklus 2 - Tenberge, Claudia; von Braunmühl, Susanne

Lebensformen, Welt, Gesellschaft. Alltagsleben, Gemeinschaft und Feste. Zyklus 2. - Tenberge, Claudia; von Braunmühl, Susanne

Ich und die anderen. Zugehörigkeit, Freundschaft und Familie. Zyklus 2. - Tenberge, Claudia; von Braunmühl, Susanne

Kultur und Kommunikation. Religion, Sprache und Verständigung. Zyklus 3. - Tenberge, Claudia; von Braunmühl, Susanne

Große Fragen. Welt und Wahrheit. Leben und Tod. Zyklus 3. - Tenberge, Claudia; von Braunmühl, Susanne

Lebensformen, Welt, Gesellschaft. Normen und Werte - Religionen und Kulturen. Zyklus 3. - Tenberge, Claudia; von Braunmühl, Susanne

Mensch, Natur, Technik. Lebenswelt, Information und Sprache. Zyklus 3. - Tenberge, Claudia; von Braunmühl, Susanne

Turn all the lights off: Bright- and dark-field second-harmonic microscopy to select contrast mechanisms for ferroelectric domain walls - Hegarty, Peter A.; Beccard, Henrik; Eng, Lukas M.; Rüsing, Michael (Journal of Applied Physics)
Recent analyses by polarization resolved second-harmonic (SH) microscopy have demonstrated that ferroelectric (FE) domain walls (DWs) can possess non-Ising wall characteristics and topological nature. These analyses rely on locally analyzing the properties, directionality, and magnitude of the second-order nonlinear tensor. However, when inspecting FE DWs with SH microscopy, a manifold of different effects may contribute to the observed signal difference between domains and DWs, i.e., far-field interference, Čerenkov-type phase-matching (CSHG), and changes in the aforementioned local nonlinear optical properties. They all might be present at the same time and, therefore, require careful interpretation and separation. In this work, we demonstrate how the particularly strong Čerenkov-type contrast can selectively be blocked using dark- and bright-field SH microscopy. Based on this approach, we show that other contrast mechanisms emerge that were previously overlayed by CSHG but can now be readily selected through the appropriate experimental geometry. Using the methods presented, we show that the strength of the CSHG contrast compared to the other mechanisms is approximately 22 times higher. This work lays the foundation for the in-depth analysis of FE DW topologies by SH microscopy.
Keywords: General Physics and Astronomy

High-speed hyperspectral imaging of ferroelectric domain walls using broadband coherent anti-Stokes Raman scattering - Reitzig, Sven; Hempel, Franz; Ratzenberger, Julius; Hegarty, Peter A.; Amber, Zeeshan H.; Buschbeck, Robin; Rüsing, Michael; Eng, Lukas M. (Applied Physics Letters)
Spontaneous Raman spectroscopy (SR) is a versatile method for analysis and visualization of ferroelectric crystal structures, including domain walls. Nevertheless, the necessary acquisition time makes SR impractical for in situ analysis and large scale imaging. In this work, we introduce broadband coherent anti-Stokes Raman spectroscopy (B-CARS) as a high-speed alternative to conventional Raman techniques and demonstrate its benefits for ferroelectric domain wall analysis. Using the example of poled lithium niobate, we compare the spectral output of both techniques in terms of domain wall signatures and imaging capabilities. We extract the Raman-like resonant part of the coherent anti-Stokes signal via a Kramers–Kronig-based phase retrieval algorithm and compare the raw and phase-retrieved signals to SR characteristics. Finally, we propose a mechanism for the observed domain wall signal strength that resembles a Čerenkov-like behavior, in close analogy to domain wall signatures obtained by second-harmonic generation imaging. We, thus, lay here the foundations for future investigations on other poled ferroelectric crystals using B-CARS.
Keywords: Physics and Astronomy (miscellaneous)